Integrating hydraulic and physiologic factors to develop an ecological habitat suitability model. (September 2020) - Shim, Taeyong; Kim, Zhonghyun; Seo, Dongil; Kim, Young-Oh; Hwang, Soon-Jin; Jung, Jinho
Abstract: This study aimed to develop an ecological habitat suitability model (EHSM) for Zacco platypus by integrating hydraulic (HHS) and physiologic (PHS) habitat suitability. Study sites (117 stations) were selected throughout the five major watersheds in South Korea, where hydraulic, water temperature, and fish survey data (2008–2015) were available. The HHS was determined using preference curves for water depth and velocity, while the PHS was determined by growth and stress curves. The geometric mean of HHS and PHS was the most appropriate to calculate the ecological habitat suitability (EHS) when compared with fish abundance. The relation of EHS was lower with PHS ( r  = 0.750) than with HHS ( r  = 0.956), likely due to the thermal tolerance of Z. platypus . EHSM represented the effect of water temperature on fish growth and stress better than a conventional model, suggesting a promising tool to estimate the habitat suitability of freshwater fish. Highlights: A new EHSM model integrated hydraulic and physiologic habitat suitability. Growth and stress curves were developed to simulate physiologic habitat suitability. The habitat suitability of Zacco platypus was evaluated on a national scale.